Future Perspectives of POSEIDON Stratification for Clinical Practice and Research - Humaidan, Peter; La Marca, Antonio; Alviggi, Carlo; Esteves, Sandro C.; Haahr, Thor (Frontiers in Endocrinology, 2019)
A total of 50 % of patients undergoing IVF treatment has previously been estimated to fulfill the POSEIDON classification criteria; importantly, although the reproductive prognosis differs between patients, POSEIDON patients share the same characteristic of a low ovarian response to exogenous gonadotropin stimulation - independent of age. POSEIDON patients require focused attention as regards ovarian stimulation in order to increase the chances of having at least one euploid blastocyst for transfer – the success criterion for stimulation set forth by the POSEIDON Group. The key to success seems to be individualization in all steps of treatment. In this perspective article we discuss the future impact of the POSEIDON stratification for daily clinical practice as well as for research.